Maternal Perspectives on and Preferences for an Enhanced Neonatal Jaundice Education Program: An Evaluation Using the Consolidated Framework for Implementation Research - Alinaitwe, Businge; Kisakye, Faith Sharon; Ayebare, Elizabeth; Ngabirano, Tom Denis (Patient preference and adherence, 2024)
Neonatal mortality is a major contributor to under-five deaths yet the main causes of these deaths are preventable. Postnatal health education programs can improve timely detection and care seeking for newborn morbidities such as neonatal jaundice (NNJ). Being a common occurrence in low-income countries, it is surprising that women do not have sufficient knowledge about NNJ. Although the knowledge can be improved through routine education programs, healthcare providers rarely engage women in evaluating such programs, which limits their uptake and sustainability.